Maxillofacial Fracture Types and their Management in 3- to 18-year-old Individuals Referred to Shariati Hospital, Tehran, Iran - xaniar mahmoudi (Tehran University of Medical Sciences, 2023)
Objectives: This study was performed to find the most common types of maxillofacial fractures and their management in 3 to 18-year-old individuals referred to the Department of Oral and Maxillofacial Surgery at Shariati Hospital in Tehran, during a 9-year period. Materials and Methods: This retrospective study evaluated the records of 319 patients with maxillofacial fractures between 2012-2020, ranging in age from 3 to 18 years. Data regarding the etiology and location of the fracture, age, gender, and treatment approach were retrieved from the archival records and analyzed. Results: A total of 319 patients were included in the study, out of which, 255 (79.9%) were males and 64 (20.1%) were females. Motor-vehicle accidents were the most common cause of trauma (N=124, 38.9%). We recorded 605 fractures and among them, the parasymphysis (N=131, 21.6%) was the most common site of isolated fractures. Type of treatment varied depending on the fracture type and degree of displacement of the broken segments. It consisted of open reduction and internal fixation, and closed reduction procedures, which included the use of arch bars, ivy loops, lingual splints, and circummandibular wirings. Conclusion: Analysis of the results revealed that the severity of injury increased with age. Older individuals had higher a number of fracture sites and experienced greater displacement of the broken segments.